2014
DOI: 10.3928/21650799-20140514-05
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia Personnel’s Knowledge of, Attitudes Toward, and Practice to Prevent Needlestick Injuries

Abstract: Anesthesia personnel are at risk for needlestick injuries (NSIs). This study evaluated the knowledge of, attitudes toward, and practice of preventing NSIs among anesthesia personnel in four Iranian university hospitals. A self-administered anonymous questionnaire was distributed to 104 anesthesia personnel. In addition, hospital infection control center records were reviewed. The prevalence of NSI among anesthesia personnel was 56.8%. Only 32.2% reported their NSI. Men were more knowledgeable about the risks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Other studies reported different awareness amongst healthcare professionals i.e. 70% by Jahangiri et al (2016) and 10% by Motavaf et al (2014). 16 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other studies reported different awareness amongst healthcare professionals i.e. 70% by Jahangiri et al (2016) and 10% by Motavaf et al (2014). 16 .…”
Section: Discussionmentioning
confidence: 92%
“…70% by Jahangiri et al (2016) and 10% by Motavaf et al (2014). 16 . 17 18 Our study further reports that 84.5% of the participants, in the operation theatre of Shalamar Hospital, are aware of correct, immediate measures to be taken after needlestick and sharp injuries.…”
Section: Discussionmentioning
confidence: 95%